Optimizing School Engagement for Students Through Group Counseling Services during a Pandemic: A Literature Review - Ainun Nadhirah; Intan Wijaya Kusumawati; Abdul Muhid (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
The covid-19 pandemic has an impact on all areas of life including education. The establishment of a distance learning system presents new challenges for schools, teachers, parents, and students at both junior and senior high school levels. This condition becomes a threat if students are unable to adjust to be involved and play an active role in the learning process. Active engagement is a personal asset for students to help adaptively overcome various challenges and academic demands in school. The provision of group counseling services is one of the efforts that can be made by the school to improve student school engagement. The purpose of this study was to find out the form of group counseling services in improving student school engagement during the pandemic. This research uses literature review method with data collection technique that collects articles and books from several bases of journal articles online. The results showed that increased school engagement of students in learning in schools can be done through the provision of group counseling services using the appropriate approach.